PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE SFAE (STUDENT FACILITATOR AND EXPLAINING) TERHADAP HASIL BELAJAR SISWA - Dongoran, Jhonas; Sianturi, Bronika Septianti (Unversitas Katolik Santo Thomas, 2022)
This study aims to determine the effect of the sfae type cooperative learning model (student facilitator and explaining) on student learning outcomes in theme 3 grade IV SD Negeri 060911 Medan T.A 2021/2022. This type of research is an experiment using a quantitative approach. This study uses a nonequivalent control group design. The population in this study were all fourth grade students of SD Negeri 060911 Medan. The sample of this research is the students of class IVb as the experimental class totaling 23 students and class IVc students as the control class totaling 25 students. From the results of the study, it was concluded that the average student learning outcomes after being given action in the experimental class was 81.30 while in the control class it was 72.56. The results of the pre-test and post-test for the experimental class and control class were normally distributed with the scores in the experimental class Pre-Test Lcount = 0.135 Ltable 0.182 and in the Post-Test Test results Lcount = 0.173 Ltable 0.182 while in the Pre-Test control class The test is Lcount = 0.124 Ltable 0.176 and the Post-Test results show that Lcount = 0.137 Ltable 0.178. For the pre-test homogeneity test Fcount = 1.756 Ftable = 2.14 and post-test homogeneity test with a significant level = 0.05. Data were analyzed by hypothesis testing using T-test with a significant level of = 0.05. From the results of hypothesis testing, it is obtained that tcount > ttable is 4.216 > 2.158 at the level of = 0.05. Therefore, Ho is rejected and Ha is accepted so that it can be concluded that